2019
DOI: 10.18267/j.pep.719
|View full text |Cite
|
Sign up to set email alerts
|

Do SMEs Face a Higher Tax Burden? Evidence from Belgian Tax Return Data

Abstract: The public debate on taxation of domestic small and medium enterprises (SMEs) versus large and multinational enterprises (MNEs) is highly relevant nowadays. Using confidential tax return data instead of financial statement data, the results indicate that domestic SMEs face on average a 1.6 and 4.8 percentage-point higher effective tax burden compared to large domestic and large MNEs respectively. This suggests that tax incentives for SMEs are inadequate to compensate for the tax advantages of large and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Taxation is a key government policy measure and, therefore, has a direct impact on the operations of SMEs and their activities [15][16][17]. Moreover, as studies have shown [18], the tax burden is higher for SMEs compared to large and multinational enterprises. Furthermore, the tax incentives that exist in most countries are inadequate to compensate for this difference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taxation is a key government policy measure and, therefore, has a direct impact on the operations of SMEs and their activities [15][16][17]. Moreover, as studies have shown [18], the tax burden is higher for SMEs compared to large and multinational enterprises. Furthermore, the tax incentives that exist in most countries are inadequate to compensate for this difference.…”
Section: Literature Reviewmentioning
confidence: 99%